Initial Evaluation, Long-Term Monitoring, and Hepatocellular Carcinoma Surveillance of Chronic Hepatitis B in Routine Practice: A Nationwide US Study. (29th September 2021) - Tran, Sally; Jeong, Donghak; Henry, Linda; Cheung, Ramsey C.; Nguyen, Mindie H.
Abstract : INTRODUCTION: Previous studies, mostly small and single center, have shown gaps in the evaluation and monitoring of patients with chronic hepatitis B (CHB) virus infection. We aimed to examine the rates and predictors of adherence to guidelines for CHB care in a large nationwide cohort. METHODS: We identified adult patients with CHB infection from the Truven MarketScan databases of commercially insured and Medicare patients with private insurance supplement (2007–2014) using International Classification of Diseases, Ninth Revision, Clinical Modification codes. The initial evaluation cohort had at least 6 months follow-up, whereas at least 12 months was required for the long-term monitoring cohort. RESULTS: We analyzed 55, 317 eligible patients with CHB infection: mean age 46 ± 12 years, 58% men, and 14.8% with cirrhosis. Over a mean follow-up of 3.2 ± 2.3 years, 55.8% had specialist (gastroenterology or infectious diseases) visits. For initial evaluation, 59% of patients received both alanine aminotransferase (ALT) and hepatitis B virus (HBV) DNA tests, whereas only 33% had ALT, HBV DNA, and hepatitis B e antigen tests, with higher frequencies among patients with specialist visits. For long-term monitoring, only 25% had both ALT and HBV DNA tests performed annually. Among patients at higher risk of developing hepatocellular carcinoma (patients with cirrhosis, male patients without cirrhosis older than 40 years, and female patients without cirrhosis older than 50), less than 40% underwent annual hepatocellular carcinoma surveillance, with 25% never receiving surveillance during the study period. Predictors of optimal initial evaluation and long-term monitoring were compensated cirrhosis (odds ratio: 1.60 and 1.47, respectively) and specialist visits (odds ratio: 1.86 and 1.31, respectively) (both P < 0.001). DISCUSSION: In this large cohort of patients with CHB infection with private insurance or Medicare with private insurance supplement, we observed poor adherence to the recommended initial evaluation and long-term monitoring. Among the predictors of adherence were specialist visits. Further efforts are needed to identify barriers and improve access to care.